DEVELOPMENT OF INTEGRATED SCIENCE LEARNING MODULES BASED ON PROBLEM SOLVING AND SCIENTIFIC LITERACY ON THE SUBJECT OF GLOBAL WARMING FOR VII GRADE JUNIOR HIGH SCHOOL STUDENTS - annisa, rifaul (Universe, 2022)
The scientific approach in the 2013 curriculum aims to improve intellectual abilities, especially students high level thinking skill, but in science learning, students thinking abilities to solve problems are still low and the application of science literacy is still not maximum. Developing an integrated science learning module based on problem solving and scientific literacy is one way to overcome this problem. The concept developed in this research is global warming. The aim of this research is to out science learning module valid and practical. In this study, the instrument used was a validation questionnaire that was filled in by two science education lecturers and two seventh class science teacher, while the practicality test was carried out by two science teachers and by students in a one to one and small group manner. The descriptive statistical analysis technique used in this study. Based on the data analysis conducted, the avarage validity value was 86,74. In the one to one stage it was 79,19, while according to the teacher and students the small group stage was 91,89 and 89,05. So in conclusion, the module developed is valid and practical for students to use as a source of independent learning.